A STUDY ON ONLINE SHOPPING BEHAVIOURS IN TIRUCHIRAPPALLI CITY MUNICIPAL CORPORATION - Muthuvel, P.; Jerome, V. Bastin (International Journal of Psychosocial Rehabilitation, 2020)
The present study is entitled as “A Study on Online Shopping Behaviours in Tiruchirappalli City Municipal Corporation”. This paper focuses on the tremendous opportunities for growth in online mode of shopping, as the users of internet are going to triple in the years to come. The responsibility of turning these users into potential shoppers squarely lies on the shoulders of the captains of these online stores. This calls for understanding and comprehending the tastes and preferences of shoppers and framing the policies, strategies and guidelines to tap these users into everlasting online shoppers. Moreover, the internet is going to rule the world in the foreseeable future. Taking these in totality, the researcher is interested to know the perceived risk of online shopping and buying behaviour of online shoppers and to identify the effect of online shopping experience, service delivery and impact on online shoppers buying behaviour. The outcomes of the present research help the online shoppers for the adoption of better shopping experience and improve their online buying behaviour. The research was a survey type, which consists of random sampling of 384 people in Tiruchirappalli district. The investigator has constructed and validated the Online Shopping beaviour Scale by self under the guidance of his research guide. Personal data sheet was prepared by the investigator. The interpretation of data was done with statistical methods in percentage analysis, mean, standard deviation and „t‟-test.